The Influence of Brand Awareness and Customer Reviews on the Purchase Decision of Pahlawan Steamed Coating Product Surabaya - Erlin Febrilianti; Liling Listyawati; Andry Herawati; Fedianty Augustinah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The rapid growth of Indonesia's tourism sector, especially in East Java, has increasingly created fierce competition between local culinary brands. Steamed coating product Surabaya, as one of the leading souvenirs, appears on a solid brand awerness representation with an authentic customer experience. This study empirically examines the influence of Brand Awareness and Customer Review on the Purchase Decision of Steamed Layer Products of Surabaya Heroes. A causal quantitative approach was applied by purposive sampling on 96 offline and online buyer respondents. Primary data was obtained through questionnaires, analyzed using multiple linear regression supported by validity, reliability, classical assumptions, and hypothesis tests. The results showed that there was a simultaneous positive influence of the two variables on the purchase decision (F = 92.484; Sig. = 0.000). Partially, Brand Awareness (t = 6.457; β = 0.485) was more dominant than Customer Reviews (t = 5.685; β = 0.427). Adjusted R² = 0.658 explains 65.8% of the variation in purchasing decisions, with the rest by other factors. These findings underscore the urgency of brand equity and digital management reviews to build consumer trust as well as competitive advantage.